“Encounters with Bodies that Fled”: A Performative Action of Shelter and Refuge (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
The article examines the performative action “Encounters with Bodies that Fled”, held in Rio de Janeiro, with Ian, the author, and Mohammed El Jazouli, a Moroccan refugee in Brazil. The performance was an encounter between them, a gesture of sharing between bodies shaped by different experiences of belonging and displacement. Through the report of the preparation and execution processes of the performance, the article discusses the implications of this encounter. Here, performative action is seen as the creation of spaces of hospitality, where the confluence of multiple alterities becomes the driving force of the action.
Keywords: performance; encounter; refuge; city